Potensi ekstrak buah ramania (Bouea macrophylla Griffith) sebagai antibakteri terhadap beberapa bakteri patogen [The potential of ramania fruit extract (Bouea macrophylla Griffith) as an antibacterial against several pathogenic bacteria] - Nadra Khairiah, S.Si.; Rais Salim (Jurnal Riset Industri Hasil Hutan, 2020)
Ramania fruit (Bouea macrophylla Griffith) is a tropical plants, as a new natural source of polyphenols. The content of these polyphenols is very abundant, especially in the seeds. The polyphenol content is widely used in the pharmaceutical world, as antibacterial ingredient. The development of natural antibacterial compounds from plants is needed to be used as a therapeutic treatment for bacterial infectious diseases. The purpose of this study is to determine the potential of ramania seed extract, seed coat and pulp against several types of pathogenic bacteria (Escherichia coli, Enterococcus aerogenes, Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella thypimurium, and Propionibacterium acnes) that generally cause disease in humans. Ramania fruit is divided into three parts, such asseeds, seed coatand pulp. Antibacterial testing was done by agar diffusion method. The concentration of the extract for antibacterial tests were 1000 ppm, 500 ppm and 250 ppm.The MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration) values were calculated using the microdilution method using 96-well micro-titre plates. The results showed that ramania seed extract had the highest antibacterial activity compared to seed coat extract and pulp. Inhibitory zone of Ramania seed extract ranged from 23-30 mm at a concentration of 1000 ppm and still had inhibition effect up to concentration of 250 ppm. MIC value of seed extract with methanol solvent was 78.13 μg/mL against three types of bacteria (P. aeruginosa, P. acnes, and S. thypimurium).